Character Education for Environmental Awareness through the Adiwiyata Program - Muhammad Khairul Yasin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2019)
The Adiwiyata program is implemented to realize responsible school members for environmental protection and management efforts through good school governance to support sustainable development. The Adiwiyata program combines learning and action, thus it provides effective methods for changing behavior. Adiwiyata School is expected to be an agent of change for the community around the school. Schools must be a model in creating a healthy and comfortable environment and become a model in realizing school citizens who are environmentally friendly and cultured. This study aims to analyze the implementation of the Adiwiyata Program in the development of environmental awareness in the Adiwiyata Mandiri School, SMAN 1 Kajen, Pekalongan Regency. This research uses a qualitative approach with case study. The research subjects were selected by purposive sampling technique, consisting of key informants and supporting informants. Data collected through observation, interviews, and documentation. The data validity technique uses triangulation of techniques and sources. The results showed that the implementation of the Adiwiyata Program was carried out in four aspects: (1) aspects of environmentally friendly school policies, (2) aspects of environment-based school curricula, (3) aspects of management of infrastructure that supports environmentally friendly schools, and (4) aspects of activity-based participatory and overall contribute positively in creating situations and conditions that support the development of environmental awareness.